2009
DOI: 10.1302/0301-620x.91b11.22292
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for the surgical treatment of periprosthetic fractures of the femur around a well-fixed femoral component

Abstract: The use of plate-and-cable constructs to treat periprosthetic fractures around a well-fixed femoral component in total hip replacements has been reported to have high rates of failure. Our aim was to evaluate the results of a surgical treatment algorithm to use these lateral constructs reliably in Vancouver type-B1 and type-C fractures. The joint was dislocated and the stability of the femoral component was meticulously evaluated in 45 type-B1 fractures. This led to the identification of nine (20%) unstable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 38 publications
(72 reference statements)
1
90
1
1
Order By: Relevance
“…No other stems have been revised. The series of Corten et al [3] included 36 B 1 fractures. A lateral plate was used in 33 hips; in the three in which the medial comminution [14]; ORIF = open reduction and internal fixation; NA = not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…No other stems have been revised. The series of Corten et al [3] included 36 B 1 fractures. A lateral plate was used in 33 hips; in the three in which the medial comminution [14]; ORIF = open reduction and internal fixation; NA = not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth exploration and comparison of fracture management is beyond the scope of this classification summary, however, numerous studies evaluating various surgical interventions are worth mentioning [1,5,6,8,11,12,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Authors have reported good results after treatment of Type B1 fractures with lateral plates without bone grafting [1,5,20], whereas others advocate the routine use of cortical strut allografts with or without plates [6,12], especially in the presence of medial cortex comminution [8]. Biomechanical analyses investigating optimal construct stiffness have led to varying recommendations of ideal constructs including: nonlocking cable plate and allograft [23], allograft-plate [22], and plate with proximal unicortical screws with or without cables and distal bicortical screws [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risk for periprosthetic fracture is increased by numerous specific factors such as increased age, cortical bone loss, and infection, the most frequent cause is loosening of the femoral prosthesis, which is noted on approximately 80% of all pre -fracture radiographs (1,2).…”
Section: Introductionmentioning
confidence: 99%